Hearing Loss in Neurological Disorders - Li, Siyu; Cheng, Cheng; Lu, Ling; Ma, Xiaofeng; Zhang, Xiaoli; Li, Ao; Chen, Jie; Qian, Xiaoyun; Gao, Xia (Frontiers in Cell and Developmental Biology, 2021)
Sensorineural hearing loss affects approximately 466 million people worldwide, which is projected to reach 900 million by 2050. Its histological characteristics are lesions in cochlear hair cells, supporting cells, and auditory nerve endings. Neurological disorders cover a wide range of diseases affecting the nervous system, including Alzheimer’s disease, Parkinson's Disease, Huntington’s disease, autism spectrum disorder, etc. Many studies have revealed that neurological disorders manifest with hearing loss, in addition to typical nervous symptoms. The prevalence, manifestations, and neuropathological mechanisms underlying vary among different diseases. In this review, we discuss the relevant literature, from clinical trials to research mice models, to provide an overview of auditory dysfunctions in the most common neurological disorders, particularly those associated with hearing loss, and to explain their underlying pathological and molecular mechanisms.